Anther culture and haploid callus induction in bc3 germplasm of sunflower (Helianthus annuus L.) - Angeles, Alejandro; Rodríguez Guzmán, Eduardo; Ramírez Serrano, Carlos; Güitrón López, María Marcela; Palmeros Suárez, Paola Andrea (Acta Universitaria, 2020)
Sunflower is the fourth important oil seed plant in worldwide production and high oil seed content. On the other hand, the haploid plants are available to get inbred lines in a short time. The aim of this study was to develop a protocol to obtain sunflower from in vitro anther culture. The basic medium used was Murashige & Skoog (MS). Two bioassays were performed: bioassay I consisted of 25 treatments with five doses of 2,4-dichlorophenoxyacetic (2,4-D) (Î¼M) and five doses of benzyladenine (BA) (Î¼M), whereas bioassay II consisted of five treatments. The obtained callus was fixed with FFA and was observed under a microscope. In bioassay I, the induction of callus appeared at 25 days in low doses with higher weight; with higher doses, the induction was present at 40 days (r = -0.95). In bioassay II, the induction appeared at 23 days with all doses, obtaining highest callus weight. Outbreaks were not induced in transplanted callus. Uninucleate pollen grains, haploid and diploid callus and cells with haploid genome were observed.